The Conditions for Long-Term Growth in Sub-Saharan Africa: China as a Model, a Contraint and an Opportunity - (:unkn) unknown (My University, 2011)
The understanding of the factors that underlie the disappointing situation of Sub-Saharan African economies over the past decades is a debated issue. The paper highlights the problems that are associated with the export structures that characterise most Sub-Saharan African economies, in particular the dependence on primary products. It assesses the constraints that are created by this export structure regarding the possibility of structural transformation, notably the risk of ‘traps’. It argues that the impact of China has become a crucial element of the conditions for growth in Sub-Saharan Africa. This impact functions according to three dimensions: i) as a conceptual framework (the ‘developmental states’); ii) as a constraint (e.g., risk of locking economies in the exporting of commodities; risks associated with contracts that link trade and investment; risks for industrial sectors); and iii) as an opportunity for growth, via increased demand and direct investment. The paper shows the intrinsic tensions between these three dimensions.
Keywords: African Research